Porpidia irrigua, a new species related to P. contraponenda. (12th May 2014) - ORANGE, Alan
Abstract: Porpidia irrigua is described as a new species; it has a white thallus, sessile apothecia, contains the depside methyl 2'- O -methylmicrophyllinate, and grows on damp siliceous rocks. It was previously included in a wide concept of P. contraponenda, but that species differs in the thicker thallus, partly immersed apothecia, and the possession of an unidentified depside in addition to methyl 2′- O -methylmicrophyllinate, which can be separated by thin-layer chromatography using Solvent System G.